2006
DOI: 10.1248/bpb.29.1508
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Contamination on the Surface of Working Tables in Ward Staff Centers and Its Preventive Methods

Abstract: We investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The findings also showed that the objects sampled host microorganisms. Many observations abound in the same direction and show that these objects in this environment are known to harbor microorganisms such as Staphylococcus, Enterococcus, Acinetobacter [ 7 , 8 ]. The results of the colony counts suggest that microbial colonization of surfaces in these two hospitals is far higher than standard surface bio-contamination values [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings also showed that the objects sampled host microorganisms. Many observations abound in the same direction and show that these objects in this environment are known to harbor microorganisms such as Staphylococcus, Enterococcus, Acinetobacter [ 7 , 8 ]. The results of the colony counts suggest that microbial colonization of surfaces in these two hospitals is far higher than standard surface bio-contamination values [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these alcohol-based towelettes are a good choice for eliminating pathogens in a laboratory environment when there is little time between student contact with the adjusting tables. 18 Microbial surveys done on a routine basis may encourage compliance with disinfection protocols. We showed that the number of bacterial colonies remained low for a 12-month period; this is possibly due to the fact that clinicians and students were aware that surveys would be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…However, the microbicidal effect of ethyl alcohol did not refl ect on microbes in fruit peel and fl esh, because the microbial counts of all samples were below the detection level. Disinfection by ethyl alcohol in hospitals has been studied to prevent cross-contamination between environmental surfaces and patients by direct or indirect contact by Oie et al (2005) and Oomaki et al (2006). They reported that disinfection by wiping with 80% ethyl alcohol eliminated Staphylococcus aureus on smooth surfaces such as examination table and working table, but not on porous surfaces made of sponge-like materials (polyethylene foam) such as stretcher for the immersion bath and shower chair.…”
Section: Effect Of Ethyl Alcohol Spraying On Microbial Decontaminatiomentioning
confidence: 99%